Rapid Fabrication of Reinforced and Cell-Laden Vascular Grafts Structurally Inspired by Human Coronary Arteries - Garcia-Herrera, C (Nature Publishing Group, 2019)
Design strategies for small diameter vascular grafts are converging toward native-inspired tissue engineered grafts. A new automated technology is presented that combines a dip-spinning methodology for depositioning concentric cell-laden hydrogel layers, with an adapted solution blow spinning (SBS) device for intercalated placement of aligned reinforcement nanofibres. This additive manufacture approach allows the assembly of bio-inspired structural configurations of concentric cell patterns with fibres at specific angles and wavy arrangements. The middle and outer layers were tuned to structurally mimic the media and adventitia layers of native arteries, enabling the fabrication of small bore grafts that exhibit the J-shape mechanical response and compliance of human coronary arteries. This scalable automated system can fabricate cellularized multilayer grafts within 30 min. Grafts were evaluated by hemocompatibility studies and a preliminary in vivo carotid rabbit model. The dip-spinning-SBS technology generates constructs with native mechanical properties and cell-derived biological activities, critical for clinical bypass applications. © 2019, The Author(s).